DIGITAL REHABILITATION IN POST-OPERATIVE RECOVERY FOLLOWING JOINT REPLACEMENT SURGERY: CURRENT EVIDENCE AND CHALLENGES - Zuzanna Przybyła,; Paweł Edyko,; Katarzyna Andrzejewska,; Wiktor Golus,; Hubert Woźniak,; Helena Szelka,; Anna Maria Gęsińska,; Krystian Czyżykowski,; Alicja Babula,; Bartosz Golis, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Digital rehabilitation has become an increasingly relevant component of postoperative care following total hip and knee arthroplasty. Its rapid growth is driven by the need for accessible, patient-centred recovery pathways and by technological progress that enables continuous home-based monitoring and guidance.Objective: The aim of this review is to consolidate recent evidence on the effectiveness, safety, patient experience, and economic impact of digital rehabilitation solutions implemented after joint replacement surgery.Methods: A narrative review of peer-reviewed studies published between 2020 and 2025 was conducted. Included research examined postoperative digital interventions such as telerehabilitation, mobile applications, wearable sensors, and virtual-reality platforms, with reported clinical, functional, adherence-related or economic outcomes. Data were synthesized qualitatively due to the heterogeneity of available technologies.Results: Digital rehabilitation consistently achieved outcomes equivalent to conventional physiotherapy across key measures of recovery, including mobility, range of motion, and patient-reported function. Wearable sensor systems provided accurate motion and activity data, enabling early recognition of atypical progress and timely clinical response. Most interventions improved adherence and user engagement by offering structured exercises, feedback mechanisms and accessible communication with clinicians. Safety profiles were favourable, and several studies reported reduced unnecessary clinic visits. Economic analyses showed that digital pathways may lower overall costs through decreased travel and reduced reliance on in-person sessions.Conclusion: Current evidence supports digital rehabilitation as an effective and efficient complement to traditional postoperative care. Its integration into standardized pathways has the potential to enhance accessibility and optimize recovery after joint arthroplasty.